Prison homicide - Long, Joshua Shane (Routledge handbook of homicide studies, 2024)
There were 143 homicides in state and federal prisons reported in 2019, and there has been an increase in homicide rate in recent years. This chapter examines death in custody trends and summarizes the scholarly theories that seek to explain prison homicides. Case studies are used to demonstrate the different motivations and methods of murder in correctional facilities. Policy implications and future research directions are discussed.